A diagnostic programmeme for student improvement: SIMPLE implementation in Faculty of Civil Engineering / Zadariana Jamil …[et al.] - Jamil, Zadariana; Alias, Rohaya; Muftah, Fadhluhartini; Ribot, Nur Marina Hani; Mohd Noor, Nur Asmaliza; Mohd Saim, Noraida; Osman, Ahmad Rasidi; Jaafar, Mohd Risham; Yaccob, Ahmad Amzari; Md Hanafiah, Jalilluddin; Alias, Asmidar; Omar, Norizah; et al. (2010)
'SIMPLE' (Student Learning Improvement Programme) was developed to motivate and to assist civil engineering students especially the students who failed civil engineering subjects and with CGPA of less than 2.3. As part of the programme, a workshop was organised by the Faculty of Civil Engineering, UiTM Pahang (FCE) by focusing on students who failed civil engineering subjects in order to enhance their understanding of the subjects and as a preparation for the coming [mal examination. This workshop was divided into four (4) divisions or sub-disciplines namely Structural and Materials, Construction, Business and Project Management, Geotechnical and Highway Engineering as well as Water Resources and Environmental System. Generally, the nature of civil engineering subjects is descriptive based, analysis-based, project-based and laboratory-based. Thus, the module of the workshop was prepared by focusing on the method of approaching the students according to the nature of the subjects, answering techniques for final examination and identification of common mistakes. Facilitators were selected among FCE lecturers. A survey was done to assess the success of SIMPLE workshop and to identify causes of subject failure. The questionnaire analysis showed that the failure of descriptive-based subjects such as Construction, Business and Project Management as well as Geotechnical and Highway Engineering was because the students had no interest in theoretical / reading subjects. In addition, the analysis for Water Resources and Environmental System as well as Structural and Materials showed that the major cause contributed to the failure was that the students had difficulties to discard laziness. Overall, SIMPLE workshop had showed a significant change (p-value < 0.05) on the students' interest on the subject, excitement of the subject, level of understanding and confidence to succeed in the subject.